(untitled) (Indian Journal of Animal Production and Management, 2016)
The objective of the study was to evaluate the effect of slatted floor in ameliorating the effects of cold stress in Black Bengal goats in Odisha. Different vital physiological signs, serum biochemical parameters, stress hormone like cortisol and browsing behaviour were studied to assess the level of stress in the two flooring pattern. Serum haptoglobin and cortisol were assayed as stress indicators in goats. Twenty adult Black Bengal goats (more than 6 months of age) were randomly selected from the Instructional Livestock Farm, OUAT and distributed into two groups (10 in each group) so that th.e mean body weight in both the groups were statistically equivalent. Statistically significant variation (P<0.05) was observed in the morning rectal temperature in control and treated groups (101.80 ± 0.13 vs. 100.54 ± 0.06 0F) in winter season. The evening rectal temperature was significantly higher (P<0.05) in control group (102.39 ± 0.07 vs. 101.07 ± 0.11 0F). Significantly higher (P<0.05) respiration rate was evident in control group than treatment during evening (25.84 ± 0.88 vs. 21.87 ± 0.79). The morning, evening and overall pulse rate showed significant lower (P<0.05) values in control than treated animals (72.91 ± 0.49 vs. 75.08 ± 0.33; 78.85 ±0.73 vs. 82.56 ±0.76 and 75.78 ± 0.58 vs. 79.27 ± 0.44) where the slatted floor was given. The heat tolerance indices of control animals were significantly lower (P<0.05) than the treated animals (0.879 ± 0.009 vs. 1.004 ± 0.007). Though the control group showed higher level of cortisol than treatment group, but that was not statistically significant. The control animals showed higher (P<0.05) level of serum haptoglobin than treatment. It can be grossly concluded that in winter, slatted floor can be a very good option to alleviate cold stress.